2022
DOI: 10.1101/2022.06.14.496192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isolation-by-distance and population-size history inferences from the coho salmon (Oncorhynchus kisutch) genome

Abstract: Coho salmon (Oncorhynchus kisutch) are a culturally and economically important species that return from multiyear ocean migrations to spawn in rivers that flow to the Northern Pacific Ocean. Southern stocks of coho salmon have significantly declined over the past quarter century, and unfortunately, conservation efforts have not reversed this trend. To assist in stock management and conservation efforts, we generated two chromosome-level genome assemblies and sequenced 24 RNA-seq libraries to better annotate th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 62 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…We then investigated historical change in effective population size using the Sequentially Markovian Coalescent in SMC++ [44] based on the 71 whole genome sequences ( Fig S2D) and both a median mutation rate of 0.8e −9 mutations/bp/generation and a mean of 1.25e −8 mutations/bp/generation as estimated for a closely related salmonid; the Atlantic salmon (J. Wang, personal communication). This analysis revealed: i) an expansion of most populations approximately 12-20 KyA, concomitant with postglacial recolonization, ii) a slow and steady decline in the Thompson R. ( Fig S2D) ), and iii) a split time between all pairwise combinations of populations (median = 16,3 KyA, range = 6,7KyA - 61KyA, Fig S3 ) compatible with the onset of postglacial population expansion following glacial retreat [38]. Using the mean mutation rate yielded more recent estimates of split times (median = 9,6 KyA, Fig S3 ) (min = 5 KyA – max = 18 KyA).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…We then investigated historical change in effective population size using the Sequentially Markovian Coalescent in SMC++ [44] based on the 71 whole genome sequences ( Fig S2D) and both a median mutation rate of 0.8e −9 mutations/bp/generation and a mean of 1.25e −8 mutations/bp/generation as estimated for a closely related salmonid; the Atlantic salmon (J. Wang, personal communication). This analysis revealed: i) an expansion of most populations approximately 12-20 KyA, concomitant with postglacial recolonization, ii) a slow and steady decline in the Thompson R. ( Fig S2D) ), and iii) a split time between all pairwise combinations of populations (median = 16,3 KyA, range = 6,7KyA - 61KyA, Fig S3 ) compatible with the onset of postglacial population expansion following glacial retreat [38]. Using the mean mutation rate yielded more recent estimates of split times (median = 9,6 KyA, Fig S3 ) (min = 5 KyA – max = 18 KyA).…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies showed that this population is highly divergent from any others [35,36,52] and displayed an increased rate of long runs of homozygosity [38]. It has been subjected to extensive hatchery enhancement (from a single population) to circumvent the decline of Coho salmon in the Thompson drainage [53].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations